PENGARUH INDUK BETINA 4 TETUA PADA REKOMBINASI GENETIK KEDELAI DI MUSIM HUJAN - Wijaya, Acep Atma; Wahyuni, Layla Fuzyanti; Karmila, Mila; Saiful, Moch.; Nugraha, Dadan Ramdani (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
The demand for soybeans in Indonesia is increasing, this is also accompanied by the development of the food industry made from soybeans. The low soybean production in Indonesia can be influenced by many factors, one of which is agro-climatology which is difficult to control, moreover, this soybean plant is a plant that is sensitive to climate change. Efforts to increase soybean production require innovation breakthroughs by assembling superior varieties to increase productivity in the rainy season. The purpose of this study was to determine the inheritance of traits from female parents or male parents to the offspring resulting from their crosses. This research was conducted in the Techno Park area of the Faculty of Agriculture, University of Majalengka which is located in Babakan Jawa, Kec. Majalengka, Kab. Majalengka which will be held from February to July 2023. The four soybean varieties used, namely Gepak Kuning, Deja 2, Mutiara 3, and Detam 4, were planted in polybags. Parameters observed were agronomic and morphological characters in crosses of soybean varieties and 4 parents. The results of this study indicate that there is low to high genetic variation. The characteristics of crosses between black soybeans and yellow soybeans are controlled by additive gene action resulting in the same genetic traits as the female parent. The maternal effect is found in the color of seeds, coat color, and coat type.